The constitution and the right of self-defence - Stewart, Hamish (University of Toronto Law Journal, 2011)
This paper explores the implications of the idea of a constitution appropriate to a liberal-democratic state for the law of self-defence. The law governing self-defence, like other laws, must also a test of substantive legality appropriate to the constitution: it must be one that could not reasonably be rejected by a person who is a member of a civil condition created with the purpose of curing the insecurities of the state of nature. While this test of substantive legality is insufficiently powerful to determine all the details of the law of self-defence, it does have several important implications. First, the positive law must recognize a right of self-defence in the core case where the defender responds with necessary and proportionate force to a wrongful threat; second, the positive law must also provide at least an excuse leading to acquittal where the defender is reasonably mistaken about one of the conditions in the core case. Furthermore, the positive law must acquit a person who uses necessary and proportionate force to repel an innocent threat because the civil condition can provide no reason for punishing such a person.